Spontaneous Volunteering in Social Crises: Self-Organization and Coordination. (April 2019) - Simsa, Ruth; Rameder, Paul; Aghamanoukjan, Anahid; Totter, Marion
This article investigates spontaneous volunteering during the social crisis referred to as the "European 2015 refugee crisis." The situation was politically controversial and the vacuum in humanitarian aid was filled by civil society, including large numbers of spontaneous volunteers (SVs). Based on empirical research, we analyzed the responses and the experiences of SVs working under the auspices of civil society organizations and derived management implications. The findings show that the environment of spontaneous volunteering in social crises differs from that in natural disaster situations. SVs partly substitute official response systems and this results in a high degree of self-organization. Thus, "structured self-organization, " that is finding a suitable complementary relationship between self-organization and coordination, is crucial for the efficiency of SVs' work, and their satisfaction, well-being, and commitment. Structured self-organization requires (a) fluid structures that enable autonomy, (b) orienting framework conditions, and (c) resources for care and coordination.